Validated Extractive Spectrophotometric Estimation of Tadalafil in Tablet Dosage Form - J. Adlin Jino Nesalin; C. Jose Gnana Babu; G. Vijaya Kumar; T. Tamizh Mani (E-Journal of Chemistry)
Two simple spectrophotometric methods have been developed for the estimation of tadalafil in both pure and tablet dosage form. Methods A and B are based on the formation of ion-pair complexes of the drug with dyes such as bromothymol blue (BTB) and bromocresol green (BCG) in acidic buffer solution followed by their extraction with chloroform to form yellow colored chromogen with absorption maxima at 420 nm and 415 nm respectively. Beer’s law is valid in the concentration range of 10-50 mcg/mL for both the methods. These developed methods were validated for precision, accuracy, ruggedness and robustness. Statistical analysis proves that the methods are reproducible and selective for the routine analysis of the said drug.